2022
DOI: 10.1021/acs.macromol.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffusive High-Pressure Hydrogen Gas Dynamics in Elastomers

Abstract: Elastomeric rubber materials serve a vital role as sealing materials in the hydrogen storage and transport infrastructure. With applications including O-rings and hose liners, these components are exposed to pressurized hydrogen at a range of temperatures, cycling rates, and pressure extremes. High-pressure exposure and subsequent rapid decompression often lead to cavitation and stress-induced damage of the elastomer due to localization of the hydrogen gas. Here, we use all-atom classical molecular dynamics si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…To investigate this further, we calculate the mean-squared displacement of all hydrogen atoms in the three systems at different temperatures (Figure ). Across each system, there is an increase in hydrogen diffusion as the temperature increases, in line with prior work . However, comparing the hydrogen MSD of the three systems at each temperature reveals interesting trends.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…To investigate this further, we calculate the mean-squared displacement of all hydrogen atoms in the three systems at different temperatures (Figure ). Across each system, there is an increase in hydrogen diffusion as the temperature increases, in line with prior work . However, comparing the hydrogen MSD of the three systems at each temperature reveals interesting trends.…”
Section: Resultssupporting
confidence: 86%
“…For each system, we find that hydrogen diffusion increases as the temperature increases, as expected. Prior work by Brownell et al has found Arrhenius dependence between hydrogen diffusion and temperature in amorphous polymers . At a temperature of 100 K, hydrogen molecules are almost completely confined in PMP and PS, with only modest mobility observed in TRP.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations